Becoming a music-centered therapist - Sorel, Suzanne (Barcelona Publishers, 2022)
Becoming a Music-Centered Therapist is a hands-on practical book designed to help students and professionals integrate--or re-integrate--their identity as a musician with their career as a music therapist. Theory, context, and step-by-step exercises combine to encourage students and practitioners in examining their relationship to music, prompting thoughtful questions about how their musical identity can expand what's possible clinically, and deepening insight into how to spark this growth in the design of their treatment plans. The author crafts clinical scenarios and musical examples to guide readers in building dynamic treatment plans that combine music with the complex needs of the human beings with whom they work. The strategies and philosophy at the heart of Becoming a Music-Centered Therapist help the reader bridge the divide between humanistic understanding and evidence-based outcomes. Language and communication choices, as well as the practical application of goals, are explored in depth. Music therapy educators will find this book's clear-cut practical framework--juxtaposed against a backdrop that crosses multiple disciplines--will work well in treatment planning, methods, practicum, internship, and clinical musicing classes and can be used repeatedly during different stages of a student's training. For music therapy practitioners, Becoming a Music-Centered Therapist offers a refreshing opportunity to consider where their own musicianship resides in their practice. Humanism, positivity, and the art and science of music therapy are explored to infuse the music therapist's sessions with new life and renewed purpose.
Keywords: Music therapy : Study and teaching